+0  
 
0
293
2
avatar+8 

https://imgur.com/yHtzC2h

 Nov 10, 2017

Best Answer 

 #1
avatar
0

6^2 / 6^-7 =6^(2 - (-7)) =6^(2 + 7) =6^9

 Nov 10, 2017
 #1
avatar
0
Best Answer

6^2 / 6^-7 =6^(2 - (-7)) =6^(2 + 7) =6^9

Guest Nov 10, 2017
 #2
avatar
0

I'm doing a math’s coaching assignment as well. I'm in my fifth year contemplating Primary Teacher Education at Brookes, Oxford. We were given a rundown of helpful math’s sites like Do My Paper For Me by our coaches.

 Nov 10, 2017

9 Online Users